科技大學教師對職能融入教學政策之接受態度研究─以「產業職能基準系統」 為中介環境 Constructing an Educational Policy Acceptance Model to Explore Attitudes Toward Policy Implementation: Using an Industrial Competency Standards System in Science and Technology Universities - 洪榮昭 Jon-Chao Hong; 張瑞娥 Jui-O Chang (Journal of Research in Education Sciences, 2018)
基於以往教育政策效益的研究，多聚焦於該領域專家的觀點，而不是從利害關係人的角度進行評估。因此，本研究目的在於建立以科技大學教師觀點之職能基準融入教學政策的接受模式。運用相關接受模式的理論主張為基礎，建構包括教師信念、政策理解性、政策執行性、政策價值性和政策接受態度等五個變項的模式，依序編製問卷、蒐集 257 份有效樣本，運用結構方程模式進行分析。研究發現：一、所建構模式適配度良好、各變項之信度與效度俱佳，可以解釋科技大學教師對職能政策的接受態度；二、本模式驗證相關接受模式的理論和成分的主張，其中構成期望成分之「政策的理解性」、「政策的執行性」，正向影響價值成分之「政策的價值性」，進而決定科技大學教師對職能政策的接受態度；三、模式中「教師的信念」對於「政策的理解性」和「政策的執行性」，具正相關；「政策的理解性」和「政策的執行性」對於「政策的價值性」，也同具正相關；而「政策的理解性」對「政策的執行性」，並無相關；四、以「教師的信念」為模式的外部變項，可提升模式的解釋力；而「政策的價值性」是模式的重要中介變項。上述的研究發現可供政策決策及執行單位參考；另本模式未來亦可擴大運用至其他對象或政策，具理論和實務的應用性。 Studies related to the effectiveness of policy making have been focused on the concerns of domain experts, not stakeholders. The purpose of this study was to construct an acceptance model of educational policy to explore competency standards integration, and technical–vocational education and teaching. Based on the perspectives of professors from science and technology universities, this study examined the correlations among teaching progressive beliefs, perceived ease of policy understanding and application, perceived value to students, and attitudes toward policy implementation. Quantitative data from 257 participants were collected for confirmatory factor analysis using structural equation modeling. The results revealed that teaching progressive beliefs was positively related to perceived ease of policy understanding and application to teaching settings; perceived ease of policy understanding and application were positively associated with value to students; and value to students was positively correlated with attitude toward policy implementation. In addition, teaching progressive beliefs positively predicted the implementation attitude that was mediated by the perceived value of policies; however, perceived ease of policy understanding and application were essential in explaining the expectancy–value research model. This study suggested that formalization of the policy acceptance model can be applied to explore other policies related to education and policy making for understanding stakeholders’ attitudes toward the implementation of new policies.